2023
DOI: 10.3389/fimmu.2023.1277491
|View full text |Cite
|
Sign up to set email alerts
|

Opioids exacerbate inflammation in people with well-controlled HIV

Christine M. Dang,
C. Mindy Nelson,
Daniel J. Feaster
et al.

Abstract: IntroductionPeople with HIV (PWH) are known to have underlying inflammation and immune activation despite virologic control. Substance use including opioid dependence is common in this population and is associated with increased morbidity and reduced lifespan. The primary objective of the present study termed opioid immunity study (OPIS), was to investigate the impact of chronic opioids in PWH.MethodsThe study recruited people with and without HIV who had opioid use disorder (OUD). Study participants (n=221) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…In OPIS, we hypothesized that PWH who have OUD would have excessive inflammation and IA, more than that caused by HIV or opioids alone. Our recent study investigated 20 cytokines as well as cellular markers of activation and exhaustion [10]. In support of our hypothesis, we found that PWH who had OUD (HIV+OP+) exhibited the highest inflammatory cytokines and cellular IA, greater than that in PWH without OUD (HIV+OP−).…”
Section: Introductionsupporting
confidence: 75%
See 4 more Smart Citations
“…In OPIS, we hypothesized that PWH who have OUD would have excessive inflammation and IA, more than that caused by HIV or opioids alone. Our recent study investigated 20 cytokines as well as cellular markers of activation and exhaustion [10]. In support of our hypothesis, we found that PWH who had OUD (HIV+OP+) exhibited the highest inflammatory cytokines and cellular IA, greater than that in PWH without OUD (HIV+OP−).…”
Section: Introductionsupporting
confidence: 75%
“…The participants for the OPIS study were recruited as described [10] by the study recruiters (Supplementary Figure S1). They were divided into four study groups based on their HIV status (HIV+/−) and OUD (OP+/−) status as HIV+OP+, HIV−OP+, HIV+OP−, and HIV−OP−.…”
Section: Study Participantsmentioning
confidence: 99%
See 3 more Smart Citations